2004
DOI: 10.1007/s10562-004-7919-3
|View full text |Cite
|
Sign up to set email alerts
|

Superacid and H-Zeolite Mediated Reactions of Benzaldehyde with Aromatic Compounds and Cyclohexane. The Role of Mono- and Dicationic Intermediates

Abstract: Reactions of benzaldehyde (1) and related compounds-3-pyridinecarboxaldehyde (9) and acetophenone with benzene, chlorobenzene, o-dichlorobenzene and cyclohexane in the presence of superacids or H-form zeolite, HUSY were (re)investigated. In accordance with previous data, 1 condenses with benzene in triflic acid (CF 3 SO 3 H) as well as on HUSY to give triphenylmethane. At elevated temperature 1 also reacts with chlorobenzene but is inert towards o-dichlorobenzene. While 1 does not react with cyclohexane in CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, according to the report, [11] the reaction rate increases with the acidity of the media. As we mentioned above, the explanations of this fact based on diprotonation of benzaldehyde [13] or protonation of the s complex 7a is inconsistent with the calculation results.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…However, according to the report, [11] the reaction rate increases with the acidity of the media. As we mentioned above, the explanations of this fact based on diprotonation of benzaldehyde [13] or protonation of the s complex 7a is inconsistent with the calculation results.…”
mentioning
confidence: 71%
“…[12] Evidently, diprotonation of carbonyl compounds having electron-withdrawing substituents is even more difficult. In a recent paper [13] an alternative explanation of enhanced reactivity of benzaldehyde with benzene in superacid media was suggested where diprotonated benzaldehyde was no longer considered as the reactive species. However, neither experimental nor theoretical evidence was given to favor this mechanism.…”
Section: Full Papermentioning
confidence: 99%
See 2 more Smart Citations
“…As such, functionalized benzocrown ethers may be readily prepared using Friedel-Crafts type chemistry. 3 We and others have recently demonstrated that the hydroxylalkylation condensation is an outstanding synthetic method leading triarylmethanes, 4 functionalized heterocycles, 5 and condensation polymers. 6 The hydroxyalkylation reaction typically involves the condensation of an aldehyde or ketone with activated aromatic compounds, such as aryl ethers or phenols.…”
mentioning
confidence: 99%